1994
DOI: 10.1128/jvi.68.6.4031-4034.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cross-neutralizing activity against divergent human immunodeficiency virus type 1 isolates induced by the gp41 sequence ELDKWAS

Abstract: Previously we identified the highly conserved amino acids Glu-Leu-Asp-Lys-Trp-Ala (ELDKWA) on the ecto-domain of gp41 as the epitope of a neutralizing monoclonal antibody (2F5) directed against human immunodeficiency virus type 1. In the present study, the sequence defining the epitope was introduced into the loop of antigenic site B of the influenza virus hemagglutinin. The resulting chimeric virus was able to elicit ELDKWA-specific immunoglobulins G and A in antisera of mice. Moreover, the distantly related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(84 citation statements)
references
References 25 publications
0
83
0
1
Order By: Relevance
“…In contrast, Bonsignori et al examined the interaction of CH01 to CH04, antibodies that recognize a complex epitope involving elements of the second and third variable regions (V2 and V3 loops) of the gp120 subunit, including an N-linked glycan at position 160, and reported that a very limited number of Envs bind the predicted germline form of this Ab (14). Also, Ma et al reported that the germline forms of MAbs 2F5 and 4E10, which target epitopes located in the membrane proximal external region (MPER) of the gp41 subunit (36,37), recognize two distinct recombinant Envs once they have been enzymatically deglycosylated (38). Overall, all currently available information suggests that recombinant Env proteins are poorly suited for engaging the predicted germline forms of bNAbs that target the CD4-BS but are relatively better suited to engage the predicted germline forms of bNAbs targeting conserved epitopes outside the CD4-BS.…”
mentioning
confidence: 99%
“…In contrast, Bonsignori et al examined the interaction of CH01 to CH04, antibodies that recognize a complex epitope involving elements of the second and third variable regions (V2 and V3 loops) of the gp120 subunit, including an N-linked glycan at position 160, and reported that a very limited number of Envs bind the predicted germline form of this Ab (14). Also, Ma et al reported that the germline forms of MAbs 2F5 and 4E10, which target epitopes located in the membrane proximal external region (MPER) of the gp41 subunit (36,37), recognize two distinct recombinant Envs once they have been enzymatically deglycosylated (38). Overall, all currently available information suggests that recombinant Env proteins are poorly suited for engaging the predicted germline forms of bNAbs that target the CD4-BS but are relatively better suited to engage the predicted germline forms of bNAbs targeting conserved epitopes outside the CD4-BS.…”
mentioning
confidence: 99%
“…Consequently, only a few neutralizing mAbs targeting gp41 are known. Most prominent are the broadly neutralizing patient-derived mAbs 2F5, 4E10, and Z13, targeting the MPER region of gp41 in the context of the viral membrane [19,[63][64][65][66][67][68][69]. Recently, a new mAb, CAP206-CH12, targeting an MPER epitope overlapping with the 4E10 epitope was identified by Ag-specific B-cell sorting [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, this region of gp41 -especially the core epitope that is recognized by monoclonal antibody 2F5 (ELDKWA) -seems to be poorly immunogenic, as antibodies specific for this epitope occur infrequently in HIV-1-infected individuals 39,40 . Moreover, experimental immunogens that consisted of the 2F5 epitope inserted into either the influenza virus haemagglutinin antigen, the hepatitis B virus surface antigen or the Escherichia coli MaIE protein failed to elicit antisera with neutralizing activity for primary isolates [40][41][42] . Therefore, this interesting epitope seems to require a particular molecular context, but this context might reduce the efficiency of its presentation to the immune system.…”
Section: • V3 Loop: a Semi-conserved Region Of Gp120 That Is Structurmentioning
confidence: 99%